STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN KESADARAN BERMEDIA SOSIAL YANG BERETIKA - Rahma jariani; Enjelita; Muzzaki Ramadhani; Hevia Gustin; Mukhtar Latif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rise of social media has brought significant changes to people’s lives, particularly among students. On the one hand, social media makes it easier to access information and communicate; on the other hand, it has also given rise to various problems, such as the spread of misinformation, hate speech, cyberbullying, and a lack of ethical conduct in digital interactions. These conditions require Islamic Religious Education (PAI) teachers to play an active role in fostering awareness of ethical social media use based on Islamic values. This study aims to analyze the strategies used by Islamic Religious Education teachers in fostering awareness of ethical social media use among students. The study employed a qualitative approach using a literature review method. Data were obtained from various scholarly sources, such as books, national and international journal articles, and documents relevant to the research topic. Data analysis was conducted through the stages of data collection, reduction, presentation, and drawing conclusions regarding the various findings from the reviewed literature. The results of the study indicate that PAI teachers’ strategies for fostering ethical social media awareness can be implemented through the integration of moral values into the learning process, setting a good example in the use of digital media, cultivating responsible digital literacy, strengthening Islamic character education, and fostering collaboration among schools, families, and the community. These strategies contribute to shaping students who are wiser, more critical, responsible, and capable of using social media in accordance with religious norms, ethics, and moral values in the digital age.